POLA MIX USE RUANG RUMAH TINGGAL PENGRAJIN BATIK DESA BABAGAN YANG BERBASIS GENDER - Titien Woro Murtini; Arief Satya Wijaya; Arlina Adiyati (TATALOKA, 2018)
The phenomenon of the living house functional change in batik craftsman settlement is the result of the transformation processes of cultural and social development that exsist in the community. Firstly the pattern of batik craftsman living houses in Babagan had a social function, and eventually almost all houses now have mixed functions; primarily as a living place for family and alternatively as a place to run the batik business.   A house that is supposed to be a living place now has additional function as a place to produce batik. The purpose of this research is to identify the pattern of living house use done by batik craftsman in Babagan village; where in this circumstance, women play their role as an effort to improve the economic condition of their families. This research employed descriptive-interpretative method to conduct the analysis, and the result showed that there was place utilization having the mixed use gender-based pattern. This pattern is a concept of a living house with mixed functions, as both living place and batik business place, without changing or adding something to its layout, and these places are interchangeably used by the women as a place to make batik. This pattern creates flexible use of a living house’s place as a gender-based business place.